NOVEL CHATTERBOT SYSTEM OF ESTIMATING CURRENT USER INTERESTS BY MEANS OF WEB INFORMATION - Ueno, Miki; Mori, Naoki; Matsumoto, Keinosuke (International Journal of Computing, 2014)
Human like conversation systems are one of the most important target of computer engineering. To achieve natural conversation, estimating current user interests is the essential issue. In this paper, we proposed the novel chatterbot which can estimate current user interests by means of Web information to solve above problem. In proposed chatterbot, interests are represented by interest vectors that were created by Bulletin Board System (BBS) data. To show the effectiveness of the proposed method, the computational experiments are carried out taking several BBS data as examples.